Respostas
respondido por:
10
2x² + 8x - 42 = 0
∆ = 8² - 4•2•(-42)
∆ = 64 + 336
∆ = √400
∆ = 20
_______________
-8 ± 20/2•2
-8 ± 20/4
x1 = -3
x2 = -7
∆ = 8² - 4•2•(-42)
∆ = 64 + 336
∆ = √400
∆ = 20
_______________
-8 ± 20/2•2
-8 ± 20/4
x1 = -3
x2 = -7
respondido por:
6
2x²+8x-42=0
∆= b²-4ac
∆= 8²-4•2•(-42)
∆= 64+336
∆= 400
-b+/-✓∆
X=-----------
2.a
-8+/-✓400
X=----------------
2.2
-8+/-20
X=-----------------
2.2
-8+20
X'=-----------------
4
12
X'=_________
4
X'=3
X''= -28
————
4
X''= -7
∆= b²-4ac
∆= 8²-4•2•(-42)
∆= 64+336
∆= 400
-b+/-✓∆
X=-----------
2.a
-8+/-✓400
X=----------------
2.2
-8+/-20
X=-----------------
2.2
-8+20
X'=-----------------
4
12
X'=_________
4
X'=3
X''= -28
————
4
X''= -7
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás